NGS-based identification of druggable alterations and signaling pathways – hepatocellular carcinoma case report - Kotelnikova, E.A.; Logacheva, M.D.; Nabieva, E.R.; Pyatnitskiy, M.A.; Vinogradov, D.V.; Makarova, A.S.; Demin, A.V.; Paleeva, A.G.; Kremenetskaya, O.S.; Penin, A.A.; Klepikova, A.V.; Kasianov, A.S.; et al. (Вiopolymers and Cell, 2015)
Aim. To identify potential cancer driving or clinically relevant molecular events for a patient with hepatocellular carcinoma. Methods. In order to achieve this goal, we performed RNA-seq and exome sequencing for the tumor tissue and its matched control. We annotated the alterations found using several publicly available databases and bioinformatics tools. Results. We identified several differentially expressed genes linked to the classical sorafenib treatment as well as additional pathways potentially druggable by therapies studied in clinical trials (Erlotinib, Lapatinib and Temsirolimus). Several germline mutations, found in XRCC1, TP53 and DPYD, according to the data from other clinical trials, could be related to the increased sensitivity to platinum therapies and reduced sensitivity to 5-Fluorouracil. We also identified several potentially driving mutations that could not be currently linked to therapies, like deletion in CIRBP, SNVs in BTG1, ERBB3, TCF7L2 et al. Conclusions. The presented study shows the potential usefulness of the integrated approach to the NGS data analysis, including the analysis of germline mutations and transcriptome in addition to the cancer panel or the exome sequencing data.